Uma abordagem da álgebra dentro do currículo do ensino fundamental: mudanças e proposta para sala de aula - Pinheiro, Bruno Reuber Maia (Universidade Federal Rural do Semi-Árido, 2019)
It is noticeable that there are numerous difficulties surrounding the teaching / learning of Mathematics. The experience in the classroom shows this, but the difficulties increase when students are faced with algebra, something that is well required, as it encourages creativity, broader vision and generalization. The following research aims to analyze the curriculum in relation to algebra, pointing out the changes made by the Base Nacional Comum Currícular (BNCC), and propose differentiated activities for everyday classroom. Readings were taken on the elementary school curriculum, analysis of the BNCC, the PCNs, textbooks, classroom experiences and application of intervention activity. Research has shown that Parâmetros Curriculares Nacionais (PCNs) divided the contents into four blocks: numbers and operations, space and shape, quantities and measures, and information processing. Algebra was discretely included in numbers and operations in the 3rd cycle (6th and 7th grade) and with more depth in the 4th cycle (8th and 9th grade). Now the BNCC brings significant changes to the field of algebra by proposing five thematic units: numbers, algebra, geometry, quantities and measures, and probability and statistics, as you can see algebra is now a thematic unit that intertwines with others, and will apply from the early years of elementary school I (1st to 5th grade) to the final years of elementary school II (6th to 9th grade), different from what PCNs recommended. Amid this change of curriculum, classroom experience proves that teaching through networking has been very effective. Curricula are changing and increasingly placing students as explorers of their own knowledge and teachers to reflect and reinvent their didactics in the classroom. The challenge now is algebra in the early years of elementary. The new textbooks from 6th to 9th grade already follow BNCC standards, merging research and cooperation activities, working algebraic thinking from an early age. Thus helping to minimize the difficulties faced in the final years.
Keywords: Álgebra,; Currículo; Pensamento algébrico; Ensino e aprendizagem; Algebra; Curriculum; Algebraic Thinking; Teaching and Learning; CIENCIAS EXATAS E DA TERRA::MATEMATICA